Updates on the Mobile Divider and Its Use in Calabria Region to Monitor and Control Aethina tumida Infestation - Camilla Di Ruggiero (MDPI AG, 2021)
The small hive beetle (SHB), Aethina tumida was first detected in the Calabria and Sicily region (Southern Italy) in 2014. In this regard, a more effective and faster inspection method than the Official one (Ministry of Health) was tested to detect the beetle in the hive. In collaboration with Calabria beekeepers’ association, a “mobile divider”-based method was tested, in order to facilitate the detection of A. tumida and save time during hive inspection. In this short communication, we provide an update on the mobile divider technique and its related inspection procedure, which was first proposed and used in Calabria (Southern Italy) from 2014 to 2016. We report preliminary data concerning the number of detected SHBs and the time spent for their detection, based on the inspection of two apiaries in Calabria region, using both methods (official method and mobile divider method). The preliminary data presented here show that, on average, the mobile divider method seems to be able to recover a slightly higher number of beetles (0.9 adults) per inspected hive, in a shorter time (25 s).